Acceptance of COVID-19 Vaccines in Sub-Saharan Africa : Evidence from Six National Phone Surveys - Kanyanda, Shelton; Markhof, Yannick; Wollburg, Philip; Zezza, Alberto (World Bank, Washington, DC, 2021)
Recent debates surrounding the lagging COVID-19 vaccination campaigns in low-income countries center around vaccine supply and financing. Yet, relatively little is known about attitudes toward COVID-19 vaccines in these countries and in Africa in particular. This paper provides cross-country comparable estimates of the willingness to accept a COVID-19 vaccine in six Sub-Saharan African countries. It uses data from six national high-frequency phone surveys in countries representing 38 percent of the Sub-Saharan African population (Burkina Faso, Ethiopia, Malawi, Mali, Nigeria, and Uganda). Samples were drawn from large, nationally representative sampling frames providing a rich set of demographic and socioeconomic characteristics which are used to disaggregate the analysis. The findings show acceptance rates to be generally high, with at least four in five people willing to be vaccinated in all but one country. Vaccine acceptance ranges from nearly universal in Ethiopia (97.9 percent) to below what would likely be required for herd immunity in Mali (64.5 percent). Safety concerns about the vaccine in general and its side effects emerge as the primary reservations toward a COVID-19 vaccine across countries. These findings suggest that limited supply, not inadequate demand, likely presents the key bottleneck to reaching high COVID-19 vaccine coverage in Sub-Saharan Africa.